Implementation of Card Media to Improve Students Learning Activities - Utami, Rosania Puji; Rezania, Vanda (Jurnal Pijar Mipa, 2025)
The lack of science learning in learning bored students, and many students are not active in learning. To overcome this, needed learning media. The card media in this study is a triangular card with questions and answers in text or images. This study aims to describe the learning steps with card media that can improve student learning activities. This study applies classroom action research consisting of two cycles. The study subjects were 28 grade VI students of UPT Satuan Pendidikan SDN Kejapanan II. Data collection tools used include interviews and guidelines for observing student learning activities. The interview technique is to find data by asking students questions verbally after learning. The interview aims to determine students' difficulties in following learning with card media. The second technique is observation, which aims to determine the completeness of student activities while learning to use card media. From these two techniques, data is obtained and then analyzed according to needs. Based on the study's results, it can be concluded that card media can improve student learning activities. In cycle I, the average score of student activity was 83.8%, while in cycle II, it was 93.3%. Thus, there was an increase of 10%. This increase can be seen from students' enthusiastic learning activities towards using card media guided by the research instrument. The suggestions submitted are: (1) To facilitate the use of card media, detailed rules should be made so that there are no errors and chaos during the implementation of using card media; (2) Card media can develop various subjects, not only science because elementary school children are very interested in the concept of learning while playing.